INTEGRASI TEKNOLOGI DALAM PENDIDIKAN AGAMA ISLAM: KONSEP, IMPLEMENTASI, DAN TANTANGAN DI ERA DIGITAL - Jaya; Uliah, Rifatul; Amir, Raihan Delpha; Mardlatillah, Aina; Saputri, Marsanda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of technology has brought significant changes to the field of education, including Islamic Religious Education (IRE). This study aims to describe the concept of technology in Islamic Religious Education, its application in the learning process, the relationship between technology and IRE learning, as well as the challenges encountered in its implementation. This research employs a library research method by examining various literature sources, including books, scientific journals, and relevant research findings. The data were analyzed using content analysis techniques to obtain a comprehensive understanding of the utilization of technology in IRE learning. The findings indicate that technology plays an important role in enhancing the effectiveness, efficiency, and attractiveness of learning through the use of visual, audio, audiovisual, and internet-based media. In addition, technology supports the development of knowledge and the strengthening of Islamic values among students. However, its implementation still faces several challenges, such as limited infrastructure, low digital literacy, curriculum adjustment issues, and concerns related to digital security and ethics. Therefore, continuous efforts are needed to optimize the use of technology in order to improve the quality of Islamic Religious Education learning in the digital era.